2022
DOI: 10.3390/app12157743
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines, Chemokines, Insulin and Haematological Indices in Type 2 Diabetic Male Sprague Dawley Rats Infected with Trichinella zimbabwensis

Abstract: Diabetes mellitus is a chronic metabolic disease induced by the inability to control high blood glucose level. Helminth-induced immunomodulation has been reported to prevent or delay the onset of type 2 diabetes mellitus (T2DM), which, in turn, ameliorates insulin sensitivity. Therefore, there is a need to understand the underlying mechanisms utilized by helminths in metabolism and the induction of immuno-inflammatory responses during helminthic infection and T2DM comorbidity. This study aimed at using a labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Kolderup and Svihus [36] reported that d-fructose can contribute negatively to blood glucose homeostasis by resulting in insulin resistance in the liver. A study by Silas and Tshilwane [17] found that rats that had a comorbidity of diabetes and T. zimbabwensis infection had an increased insulin level on day 35 post-infection when compared to the diabetic group. Additionally, the observed increase was said to be via the insulin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolderup and Svihus [36] reported that d-fructose can contribute negatively to blood glucose homeostasis by resulting in insulin resistance in the liver. A study by Silas and Tshilwane [17] found that rats that had a comorbidity of diabetes and T. zimbabwensis infection had an increased insulin level on day 35 post-infection when compared to the diabetic group. Additionally, the observed increase was said to be via the insulin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite species that have been studied to have shown delays in the onset of hyperglycemia in rats include Syphacia muris [16]. Silas and Tshilwane [17] conducted a study on the comorbidity of Trichinella zimbabwensis and T2DM in Sprague Dawley rats and reported low blood glucose and increased insulin levels in animals that were diabetic and infected with T. zimbabwensis. However, the metabolite shifts in the animals were not studied, except for their glucose indices.…”
Section: Introductionmentioning
confidence: 99%